African Postcolonial Modernity : Informal Subjectivities and the Democratic Consensus - Osha, Sanya; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
African cultures and politics remain significantly affected by precolonial and postcolonial configurations of modernity, as well as hegemonic global systems. This project explores Africa's conversation with itself and the rest of the world, critiquing universalist notions of democratization.
Keywords: Science; Science; Science, general